Urgensi yang Harus diperhatikan dalam Dunia Pendidikan - Af'idatun Nafiah (LPPM IAI Hasanuddin Pare-Kediri, 2020)
ABSTRACTEducation has the right to be obtained by anyone especially those who excel but have not been able to finance education. Education can be obtained from various places from formal and non-formal. There are many interests that must be considered in education. Among them that must be considered are growth in education, must have motivation with good goals, psychology in education, factors that influence the quality of education. Facility costs and also friends also greatly influence the development of education. There are so many ways that can be done in gaining knowledge including methods such as discussions, groups, forums, questions and answers, assignments, demonstrations and so forth.